2013
DOI: 10.1111/jar.12058
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial Motivation, Stress and Burnout Among Direct Support Workers

Abstract: Prosocial motivation plays an important role in explaining the relatively low levels of DP in the sector. The study advances our understanding of the key components of burnout among direct support workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Recent research is consistent with these ideas. For example, Hickey () conducted a large study among Canadian disability service providers and tested the moderating role of prosocial motivation in the relationship between job demands (role stressors) and burnout. The results showed that prosocial motivation buffered the positive impact of role boundary stress on depersonalization and the negative impact of role ambiguity on personal accomplishment.…”
Section: A Job Demands–resources Approach To Psmmentioning
confidence: 99%
“…Recent research is consistent with these ideas. For example, Hickey () conducted a large study among Canadian disability service providers and tested the moderating role of prosocial motivation in the relationship between job demands (role stressors) and burnout. The results showed that prosocial motivation buffered the positive impact of role boundary stress on depersonalization and the negative impact of role ambiguity on personal accomplishment.…”
Section: A Job Demands–resources Approach To Psmmentioning
confidence: 99%
“…Burnout is studied extensively relative to human service workers and the literature repeatedly discusses the emotional nature of the work as a key contributor for emotional exhaustion that may also result in turnover intention or turnover (Hewitt & Lakin, 2001;Hickey, 2014;Morse, Salyers, Rollins, Monroe-DeVita, & Pfahler, 2012). While existing literature covers the relationship of emotional labor to burnout, there is a gap pertaining to this for human services employees providing services to individuals with disabilities.…”
Section: Burnout Within Human Servicesmentioning
confidence: 99%
“…Emotional labor is explored in the current study using the three focal lenses (occupational requirement, emotional displays at work, and intrapsychic experiences), as described by Grandey, Diefendorff, and Rupp (2013). Existing research including human services organizations identifies the work outcome factors of job satisfaction, burnout, and turnover intention as critical areas of concern as it relates to employee well-being and general organizational performance (Hickey, 2014;Lizano, 2015;Selden & Sowa, 2015;Skirrow & Hatton, 2007). The current study addresses this by including emotional labor (through the three focal lenses) as a component relating to and influencing job satisfaction, burnout, and turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…Care and support workers provide a service which is integral to the maintenance of their service users' lives (Ravalier et al, 2017). However, while studies have investigated the sources of stress, and influence of stress on well-being and other related outcomes, such as burnout in Australia (e.g., Judd et al, 2017) and Canada (Hickey, 2014), no such investigations have been conducted in the United Kingdom (Ravalier et al, 2017). Additionally, while there is a good understanding of the influence of contractual conditions such as temporary (Quesnel-Vallee et al, 2010) and shift working patterns (Kivimaki et al, 2011) on health, little has been looked into with respect to zero-hours contracts.…”
Section: Care and Support Worker Stressmentioning
confidence: 99%